Correlation between STEM Knowledge and STEM Teaching Practice: A Study of Mathematics Teachers' Professional Development - Marfuah Marfuah; Muda Nurul Khikmawati (Indonesian Journal of Mathematics Education, 2023)
This research aims to investigate the relationship between mathematics teachers' knowledge of STEM (Science, Technology, Engineering, and Mathematics) education and their teaching practice in schools during a STEM professional development program. The study involved 34 Indonesian mathematics vocational high school teachers enrolled in the STEM professional development program. Tests and reports on STEM teaching practices served as data sources for this study. Our finding shows a positive correlation between mathematics teachers' STEM knowledge and how they facilitate STEM project-based learning for their students. We discuss two different points of view to interpret this result. Furthermore, we suggest the need for further research to develop sustainable efforts in strengthening the STEM education interdisciplinary approach for the professional development of mathematics teachers.